2022-RA-221-ESGO Hysterectomy alone vs. hysterectomy plus sentinel node mapping in endometrial cancer: long-term results from a multi-institutional study. (20th October 2022) - Bogani, Giorgio; Donato, Violante Di; Papadia, Andrea; Buda, Alessandro; Casarin, Jvan; Ghezzi, Fabio; Angioli, Roberto; Plotti, Francesco; Luvero, Daniela; Landoni, Fabio; Panici, Pierluigi Benedetti; de Iaco, PierAndrea; et al.
Abstract : Introduction/Background: To compare outcomes after hysterectomy and hysterectomy plus sentinel node mapping (SNM) in endometrial cancer (EC) patients. Methodology: This is a retrospective study, collecting data from EC patients treated between 2006 and 2016 in nine referral centers. Results: The study population included 398 (69.5%) and 174 (30.5%) patients having hysterectomy and hysterectomy plus SNM. As the results of the adoption of a propensity-score matched analysis, we selected two homogeneous cohorts of patients (150 having hysterectomy only vs. 150 having hysterectomy plus SNM). The execution of sentinel node mapping correlated with longer operative time, but it is not influencing the length of hospital stay and estimated blood loss. Overall severe complication rates were similar between groups (0.7% in the hysterectomy group vs. 1.3% in the hysterectomy plus SNM group; p=1.00). No lymphatic-specific complication occurred. Overall, 12.6% of patients having SNM were diagnosed with disease harboring in their lymph nodes. Adjuvant therapy administration rate was similar between groups. Considering patients having SNM, 4% of patients received adjuvant therapy on the basis of nodal status only; all the other patients received adjuvant therapy on the basis of uterine risk factors. Five-year disease-free (p=0.720) and overall (p=0.632) survival was not influenced by the surgical approach. Conclusion: Hysterectomy (with or without SNM) is a safe and effective method for managing EC patients. Potentially, these data support the omission of side-specific lymphadenectomy in case of unsuccessful mapping. Further evidence is warranted to confirm the role of SNM in the era of molecular/genomic profiling.